Experience with cryogenic operation of Accelerator Module Test Facility during testing of one third of XFEL cryomodules. Issue 1 (November 2015) - Anashin, V; Belova, L; Bozhko, Y; Escherich, K; Petersen, B; Putselyk, S; Pyata, E; Schnautz, T; Swierblewski, J; Zhirnov, A
Abstract : In order to produce pulsed electron beam with the energy of 17.5 GeV, the XFEL linear accelerator is under construction. After the assembly but before being installed in the accelerator tunnel, 100 accelerator modules have to be tested in Accelerator Module Test Facility (AMTF). Two vertical cryostats and three horizontal test benches are devoted to the testing of cavities and cryomodules as well as two other cold boxes and liquid helium (LHe) storage tank are installed to enable their operation. This paper describes our experience with cryogenic operation of AMTF after two years of operation.